Arabidopsis thaliana FANCD2 Promotes Meiotic Crossover Formation. Issue 2 (19th January 2018) - Kurzbauer, Marie-Therese; Pradillo, Mónica; Kerzendorfer, Claudia; Sims, Jason; Ladurner, Rene; Oliver, Cecilia; Janisiw, Michael Peter; Mosiolek, Magdalena; Schweizer, Dieter; Copenhaver, Gregory P.; Schlögelhofer, Peter
Abstract : AtFANCD2 promotes noninterfering COs in a MUS81-independent manner as part of a meiotic CO-promoting mechanism. Abstract: Fanconi anemia (FA) is a human autosomal recessive disorder characterized by chromosomal instability, developmental pathologies, predisposition to cancer, and reduced fertility. So far, 19 genes have been implicated in FA, most of them involved in DNA repair. Some are conserved across higher eukaryotes, including plants. The Arabidopsis thaliana genome encodes a homolog of the Fanconi anemia D2 gene ( FANCD2 ) whose function in DNA repair is not yet fully understood. Here, we provide evidence that At FANCD2 is required for meiotic homologous recombination. Meiosis is a specialized cell division that ensures reduction of genomic content by half and DNA exchange between homologous chromosomes via crossovers (COs) prior to gamete formation. In plants, a mutation in AtFANCD2 results in a 14% reduction of CO numbers. Genetic analysis demonstrated that AtFANCD2 acts in parallel to both MUTS HOMOLOG4 ( AtMSH4 ), known for its role in promoting interfering COs and MMS AND UV SENSITIVE81 ( AtMUS81 ), known for its role in the formation of noninterfering COs. At FANCD2 promotes noninterfering COs in a MUS81-independent manner and is therefore part of an uncharted meiotic CO-promoting mechanism, in addition to those described previously.